Separation of middle boiling trace compounds by distillation: An investigation of practical implications of complex column arrangements on an industrial methanol distillation case study. Issue 1 (14th October 2020) - Udugama, Isuru A.; Kirkpatrick, Robert; Yu, Wei; Gernaey, Krist V.; Young, Brent R.; Bayer, Christoph
Abstract: The drive to achieve greater energy efficiencies is well‐established in the fine chemical industries with distillation processes being a key focus due to their disproportionate energy consumption totaling more than 40% of the overall plant. The objective of this paper is to specifically focus on the energy efficiency benefits that would be realized by employing intensified distillation column configurations on a high purity, multicomponent, high recovery industrial methanol distillation where a middle boiling trace ethanol component must be managed to ensure on specification production (<10 ppm wt. ethanol in product and <5 ppm impurities in bottoms). Based on technology maturity constraints, five column configurations were selected for further analysis, comprising a direct synthesis configuration, a side draw column, a Petlyuk inspired recovery column arrangement, a divided wall column, and a cut divided wall column. These configurations were then simulated on an industrial process simulator where all configurations were able to match the strict industrial product specifications and design limits. The energy usage of the column configurations was improved through a systematic analysis, and the results revealed that all intensified columns have a superior energy usage compared to the direct synthesis configuration but with the gains limited to only 3%. An unbiased consideration of the energy efficiency results, together with other external factors including cost of capital and operability, shows that the recovery column configuration would be the most practical choice despite the presence of the divided wall column configuration which represents a greater level of intensification and integration.